Seeking freedom in the “third space” of diaspora: Muslim women's identity in Aboulela's Minaret and Janmohamed's love in a headscarf - Hasan, Md. Mahmudul (Routledge Taylor & Francis Group, 2015)
Muslim societies, and especially Muslim women, have often received fetishized attention in (neo-)Orientalist literature. However, opening up spaces for the voices of Muslim women especially those wearing the hijab is long overdue. Therefore, the representation of diasporic Muslim women and their multiple identities in Leila Aboulela’s Minaret and Shelina Janmohamed’s Love in a Headscarf is of paramount importance. These two texts show how, face to face with possibilities and pitfalls of diaspora, Muslim women negotiate and prioritize Islamic identity in the metropolis. While immigrant Muslim men are racked with somewhat unacknowledged exilic anxieties, the challenge and possibility of Muslim women largely concern gender and religion. For a group of Muslim women, the West facilitates a critical interrogation of their feeling of identity vacillation and creates a useful framework for thinking about their religious observances, which eventually helps them conceptualize and articulate their sense of belonging. For many others, it provides a third space in which they can confidently engage in a reinterpretation of the Islamic texts and thus reclaim an identity which liberates them from culturally enacted practices of their countries of origin.